Little mouse - Murray, Alison (Disney/Hyperion Books, 2013)
A little girl explains how she does not always fit her nickname, little mouse, but it is perfect for when she is cuddling with her mother
Keywords: Nicknames; Mother and child; Kind; Übername; Mutter; Bilderbuch